Development of novel murine mammary imaging windows to examine wound healing effects on leukocyte trafficking in mammary tumors with intravital imaging. Issue 1 (2nd January 2016) - Sobolik, Tammy; Su, Ying-Jun; Ashby, Will; Schaffer, David K.; Wells, Sam; Wikswo, John P.; Zijlstra, Andries; Richmond, Ann
ABSTRACT: We developed mammary imaging windows (MIWs) to evaluate leukocyte infiltration and cancer cell dissemination in mouse mammary tumors imaged by confocal microscopy. Previous techniques relied on surgical resection of a skin flap to image the tumor microenvironment restricting imaging time to a few hours. Utilization of mammary imaging windows offers extension of intravital imaging of the tumor microenvironment. We have characterized strengths and identified some previously undescribed potential weaknesses of MIW techniques. Through iterative enhancements of a transdermal portal we defined conditions for improved quality and extended confocal imaging time for imaging key cell-cell interactions in the tumor microenvironment.